Menuju Kemasan Produk UMKM yang Menarik dan Informatif: Pelatihan Desain Kemasan di Desa Galengdowo - Maria Helena Putri Madyoratri; Indah Respati Kusuma Sari (Institut Nalanda, 2024)
The development of household industries, like those managed by Pak Miskan and Ibu Wati in Desa Galengdowo, has seen a rise in quantity but lacks improvement in quality, particularly in branding and marketing strategies. Effective labeling and packaging, crucial for product identity and consumer attraction, remain underdeveloped. Recognizing the need for improvement in these areas, a training program on product packaging design was conducted for local micro, small, and medium enterprises (MSMEs). This initiative aimed to enhance the visual appeal and information content of product packaging, thereby boosting market competitiveness. The involvement of UPN students in this economic activity is expected to drive innovation and creativity among the community members. The main challenge identified was marketing, with local MSMEs primarily selling their products in nearby shops and food stalls. To address this, leveraging social media platforms like Instagram and Facebook was proposed. The integration of modern technology and information into business practices is essential for MSMEs to adapt and thrive in a competitive environment. Improved packaging and labeling, combined with strategic marketing, can significantly enhance brand awareness, product appeal, sales, and brand image. This training program aims to empower MSMEs in Desa Galengdowo, enabling them to develop distinctive, attractive, and informative product packaging that meets consumer preferences, ultimately contributing to economic growth at the local level.